2011
DOI: 10.1016/j.apnr.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Online research in older adults: lessons learned from conducting an online randomized controlled trial

Abstract: The Internet has revolutionized healthcare delivery. With the increasing number of online users and the advancement of eHealth technologies, many healthcare studies have been conducted online. However, online research is still a relatively new field, and many methodological issues still need to be investigated. Over the years, the authors have conducted studies on various aspects of online health intervention research, including development and usability testing of online health interventions, web surveys, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Using a well-prepared moderator for the discussion boards can also be helpful, as he or she can direct the group members’ discussions toward the goals of the study and provide encouraging comments (Cudney & Weinert, 2000). We have used moderated discussion boards successfully in our prior work (Nahm et al, 2011; Nahm, Resnick, Grezia, & Brothemarkle, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Using a well-prepared moderator for the discussion boards can also be helpful, as he or she can direct the group members’ discussions toward the goals of the study and provide encouraging comments (Cudney & Weinert, 2000). We have used moderated discussion boards successfully in our prior work (Nahm et al, 2011; Nahm, Resnick, Grezia, & Brothemarkle, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…A majority of older adults report positive attitudes towards technology, including the internet, email, text messaging and smartphones [9,43,67,91]. A large ethnographic study in Ireland demonstrated that older adults adapted to waves of new technologies across their lifetimes, suggesting a higher level of acceptance and readiness than previously assumed [92].…”
Section: Attitudes Towards and Motivations To Use Technologymentioning
confidence: 91%
“…Older adults tend to use the internet for health purposes [42][43][44]. A national survey revealed that, among Baby Boomers, about half go online for some health related purpose [40], such as ordering prescriptions or obtaining health information.…”
Section: Internet and Emailmentioning
confidence: 99%
“…Thus, frequent verbal or written follow up and prompting may be necessary during the extent of a study. Any written materials provided for subjects should be presented concisely and in large print in order to increase participant understanding of instructions, study aims, and protocols (Laird & Conn, 1996; Nahm, et al, 2009). Furthermore, options for alternative forms of communication and information delivery, such as oral and visual demonstrations, should be considered if literacy levels of older adult subjects preclude written materials.…”
Section: Methodological Issuesmentioning
confidence: 99%